Pengetahuan, Sikap dan Peran Kader Remaja dalam Pencegahan Stunting - Handayani, Fatiah; Gunawan, Hendra; Sholahudin, Fauzan; Zulfa, Salsa Billah Khoeru (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the knowledge, attitudes, and roles of Muhammadiyah youth cadres in preventing stunting in the Bandung district. The study applies a Mixed Method with a convergent design. Both quantitative and qualitative data collection are conducted simultaneously. Quantitative research is carried out among all Muhammadiyah Youth Cadres through questionnaire distribution, while qualitative research involves interviews with the leaders or secretaries of the AMM organization. Knowledge and attitudes are analyzed using frequency distribution. Codes and categories are created to analyze qualitative data on the roles of cadres. The research results show that most respondents have insufficient knowledge (83%) and have relatively good attitudes towards stunting prevention (56%). The study finds that youth have limited roles as agents of socialization in stunting prevention. In conclusion, most respondents lack knowledge, have relatively good attitudes, and the roles of the cadres are as agents of socialization. Socialization should be carried out to equip the cadres to fulfil their roles in the AMM organization. Key Words: Youth Cadre, Role, Knowledge, Attitude, Stunting